The Role of human SLC19A3-mediated Intestinal Absorption in Thiamine Metabolism - Tao, Tianyi. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Andrew Greenberg.; Keyword: Pharmacology.